2022
DOI: 10.3390/ijms23105815
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances of m6A Demethylases Inhibitors and Their Biological Functions in Human Diseases

Abstract: N6-methyladenosine (m6A) is a post-transcriptional RNA modification and one of the most abundant types of RNA chemical modifications. m6A functions as a molecular switch and is involved in a range of biomedical aspects, including cardiovascular diseases, the central nervous system, and cancers. Conceptually, m6A methylation can be dynamically and reversibly modulated by RNA methylation regulatory proteins, resulting in diverse fates of mRNAs. This review focuses on m6A demethylases fat-mass- and obesity-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 134 publications
(205 reference statements)
0
27
0
Order By: Relevance
“…Secondly, the primary prerequisite for targeting m6A-modified enzymes is the resolution of the protein crystal complexes of these enzymes in order to mine and design docked high-affinity small molecules and antibodies by conformational relationships ( Oerum et al, 2021 ). These inhibitors and antibodies, in turn, will be considered to provide a good pre-requisite for clinical targeting only after effective validation in cellular and animal experiments ( You et al, 2022 ). Finally, numerous studies have explained the critical role of m6A recognition proteins in BC, but a considerable number of m6A regulators have not been fully validated, including RBM15/RBM15B, HAKAI, ZC3H13, ALKBH3, eIF3, hnRNPC, and hnRNPA2B1.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the primary prerequisite for targeting m6A-modified enzymes is the resolution of the protein crystal complexes of these enzymes in order to mine and design docked high-affinity small molecules and antibodies by conformational relationships ( Oerum et al, 2021 ). These inhibitors and antibodies, in turn, will be considered to provide a good pre-requisite for clinical targeting only after effective validation in cellular and animal experiments ( You et al, 2022 ). Finally, numerous studies have explained the critical role of m6A recognition proteins in BC, but a considerable number of m6A regulators have not been fully validated, including RBM15/RBM15B, HAKAI, ZC3H13, ALKBH3, eIF3, hnRNPC, and hnRNPA2B1.…”
Section: Discussionmentioning
confidence: 99%
“…A number of compounds targeting m 6 A writers 345 , 393 and erasers 394 , 395 , 396 have been identified. A summary of these small molecules is provided in Table S5 .…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Drugging the m 6 A-and A-to-I-related pathways in cardiovascular diseases A number of compounds targeting m 6 A writers 345,393 and erasers [394][395][396] have been identified. A summary of these small molecules is provided in Table S5.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Collectively, with a minor influence on normal hematopoiesis, ALKBH5 is considered as a crucial therapeutic target for leukemia. The crystallographic and biochemical studies indicated that the ALKBH5 inhibitors may be smaller in size than those for FTO, due to its smaller active cavity [142]. Selberg et al assessed the antiproliferative effects of ALKBH5 inhibitors and discovered two compounds with potent inhibition against the proliferation of three leukemia cell lines, demonstrating the value of ALKBH5 inhibitor as an anti-leukemia strategy [143].…”
Section: Alkbh5mentioning
confidence: 99%